Pengaruh Kinerja Keuangan dan GCG Terhadap Struktur Modal (Studi Kasus Pada Perusahaan Sektor Financial yang terdaftar di BEI tahun 2020 – 2023) - Suhandi, Sherinka; Nilwan, Afrizal (Sekretariat Pusat Lembaga Komunitas Informasi Teknologi Aceh, 2025)
Capital structure, specifically referring to companies in the financial sector for 4 years from 2020 to 2023. The sample of this study used purposive sampling, and obtained 12 financial sector companies on the special monitoring board officially listed on the Indonesia Stock Exchange (IDX) for the 2020-2023 period. This study uses a descriptive method with a quantitative approach. Then the data analysis was carried out using the multiple linear regression analysis method using SPSS software version 17.0. The results of the study found that the profitability variables, the size of the board of commissioners and the audit committee had a positive effect on the capital structure. While the liquidity variable did not have a significant effect on the capital structure.